Antioxidant and antiproliferative activities plygonum minus alpinia galanga and etlingera elatior / Mohamad Zakkirun Abdullah - Mohamad Zakkirun, Abdullah (2015)
The Malaysian traditional vegetables Polygonum minus (Kesum), Alpinia galanga (Lengkuas) and Etlingera elatior (Bunga Kantan) are commonly used in local cuisines and traditional medicine. In this study, antioxidant and anti-proliferative activities of extracts from these herbs were evaluated. This may provide insights on their nutritional and medicinal values. The herbs were dried and extracted sequentially using solvents of varying polarity (apolar to polar: hexane (HX) > ethyl acetate (EA) > methanol (MeOH) > water (W). The antioxidant potential was evaluated through these assays: Total Phenolic Content (TPC), Total Flavonoid Content (TFC), Ferric Reducing Antioxidant Power (FRAP), 2,2' -azinobis (3-ethylbenzothiozoline-6-sulphonic acid) (ABTS-+), 2,2-diphenyl-1-picryld ydrazyl (DPPH"), superoxide anion (02 •-)-scavenging, nitric oxide (NO")-scavenging and ferric ion-chelating (FIC) assays. The plant extracts were evaluated for their anti-proliferative activity through MTT assay using colon cancer cell line HCTl 16, with CCD841 as the non-cancerous cell line for comparison. The apoptosis-inducing property of selected extracts was evaluated using Apotox-Glotm Triplex assay. Overall, the methanol extract of P. minus showed the most prominent antioxidant activity, demonstrating the highest values for TPC, TFC, FRAP, ABTS, DPPH and nitric oxide scavenging capacities. P. minus's water extract also gave the highest value in 02•--scavenging assay. The methanol extract of E. elatior had the highest FIC activity. Polyphenols and flavonoid contents showed a strong positive correlation with antioxidant activities, suggesting their significant contribution to the observed antioxidant activity. LCMS-IT-TOF analysis for methanol extract of P. minus identified six flavonols (quercetin and kaempferoJ), a fJavone (apigenin) and tannins. The following extracts showed selective cytotoxicity on HCT116 cells with the corresponding ICso values: PM-HX (40.00±2.04 μg/mL), PM-EA (43.18± 1.63 μg/mL) and AG-EA (71.94±1.80 μg/mL). The apoptosis assay revealed that the AG-EA extract was able to induce a 30% increase in caspase 317 activity. This study demontrates that traditional herbs could be a potential source of natural antioxidant and anticancer compounds.